Mawlid An-Nabi Celebration Across Different Countries in Cultural Dimension Aspects - Widianingsih, Karomah; Jelang Ramadhan; Muhammad Fuad; Raul Gonzales (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Mawlid an-Nabi is an annual event held on the 12th of Rabi' al-Awwal to commemorate the birth of Prophet Muhammad (PBUH). Many countries around the world organize Mawlid al-Nabi celebrations with their own cultural characteristics. This study aims to provide an overview of Mawlid al-Nabi celebrations in various countries from a cultural perspective. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework was applied to facilitate the data screening process. Study objects were obtained from online databases such as JSTOR, Scopus, The Lens, Proquest, and Google Scholar using Boolean operators, and data analysis was conducted using cultural theories by Koentjoroningrat and Geert Hofstede. This study reviewed 16 studies from 16 different countries. The findings indicate that most countries celebrating Mawlid an-Nabi reflect aspects of large power distance and dominant collectivism. Additionally, all cultural elements of the societies contribute to the diversity of Mawlid an-Nabi celebrations. In terms of celebration rituals, there are two distinct approaches: inclusive and exclusive. These two methods are practiced in both majority and minority Muslim countries. Variations in interpretations and perspectives of Sharia law among Muslim communities result in differing views and controversies regarding the celebration of Mawlid an-Nabi. The widespread and varied celebrations of Mawlid an-Nabi in various countries highlight the cultural richness of the Muslim community, particularly as a tribute to the birth of Prophet Muhammad (PBUH), despite some Muslim communities opposing it due to differing viewpoints.